Developing a Leadership for Sustainability Learning Network: Some theoretical, pragmatic and purpose-ful considerations - Blantern, Chris; Hodgson, Vivien; Marshall, Judi (Proceedings of the International Conference on Networked Learning, 2010)
This poster session explores some of the ideas and practices we are working with in a project to develop a Leadership for Sustainability Learning Network (LSLN). The aim is to initiate and support an active and vibrant online Learning Network(s) for people across different sectors in the North West region of the UK. Our aspiration is to see how far we can take the possibilities and opportunities offered by the approach and ideas of networked learning to support individuals or groups who are seeking to take leadership and bring about change in respect to sustainability, operating at the local and regional level within a global context of concerns about climate change, peak resources, social justice and associated challenges. We will explore the relationship between theoretical networked learning principles and processes (including how they are situationally privileged), an unfolding, reflexive sense of what we are trying to make happen (with reference to practical, ethical, pedagogical and political expectations), and the joint and several purposes of potential LSLN participants and their existing relational networks. Principles and practices of action research have significantly influenced our approach and the kinds of developmental engagement we are seeking to offer network participants. We will explain how our informing considerations have been reviewed in the light of changing contextual circumstances. We will outline how these have become characterised in the design, testing and use of the learning network so far. And we will consider what ongoing considerations need to be embraced in the continuing development and coherence of the leadership for sustainability learning network. The Poster at the conference will demonstrate in particular how we have begun to put a series of networked learning design principles into practice within a Leading on Sustainability programme and the key challenges and issues that we are meeting and working with.